Reducing the toxicity of diesel engines through the use of liquefied petroleum gas (LPG) - Lira Cacho, Guillermo (2018)
A new method of supplying liquid petroleum gas (LPG) in diesel engines with internal formation of air-fuel mixture to decrease the smoke and toxicity of exhaust gases is proposed. To make the comparison of toxicity in different engines, the conventional sum toxicity of total emissions is used. This last takes into account the degree of toxicity of each component of the exhaust gases. The tests let us determine that the sum toxicity of the diesel engines with the LPG supply system is less than in the cases of conventional diesel-gal engines (with external formation of the air-fuel mixture) and in diesel engines, in the ratio 0,75/0,9/1,0, respectively.